Пейоративи дурень / дурний в епістолярному автопортретуванні Тараса Шевченка - Богдан, Світлана; Bogdan, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто важливий елемент будь-якого автопортретування – оцінні компоненти, диференційовані узвичаєно на три основні різновиди: меліоративи, нейтральні оцінки, пейоративи. З огляду на те, що типова самооцінка орієнтована передусім на нейтральний і негативно маркований вимір, цілком передбачувано в епістолярному автопортретуванні саме останній різновид виявився одним із частотних, що стверджує загальномовні вияви таких оцінок у текстах інших функціональних стилів. Основну увагу зосереджено на вербалізації номінативного ряду самонайменувань-оцінок дурень / дурний, на семантичних ознаках цього концептуального для кожної національно-мовної картини світу поняття в листах Тараса Шевченка та способах актуалізації найпоширеніших побутових моделей цього концепту. In this paper the important elements of any self-portraiting such as estimating components, usually differentiated to three basic types: melioratives, neutral estimations and peioratives were observed. On the basis of the fact that typical self-esteem is oriented, first of all, to the neutral and negative-marked determination; completely forecasted in epistolary self- portraiting is exactly the last type, turned out as one of the frequency, confirming overall language tendentions of such estimations in the texts of other functional styles. The main attention is paid to the verbalization of the nominative line of the self-nominations-estimations ‘fool / stupid’, the semantic features of its conceptual (for each national-language picture of the world) concepts in Taras Shevchenko’s letters and the means of actualization of the most spreading everyday models of this concept. The stereotypic contexts and presuppositive conditions of its appearance in epistolary texts, i.e. the motivators, which are fit to defined emotional addresser’s states and correlated with the irony as the style dominant of defined letter, are assigned. The part of such estimations belongs to Shevchenko’s addressees and his familiar people. Facultatively such peioratives define the geterostereotype features of Russians with respect to Ukrainians.
Peioratyvs ‘Fool / Stupid’ in Taras Shevchenko’s Epistolary Self-Portraiting
Keywords: оцінка; пейоратив; дурень; дурний; епістолярний текст; Тарас Шевченко; estimation; peiorative; fool; stupid; epistolary text; Taras Shevchenko